Modelling and Simulation of Milk Production System of Dairy Goats in Malaysia - Hassan, Mohammad Nasir (1998)

(untitled)
The main purpose of this study was to construct a model for goats ' milk production in Malaysia. Apart from that, the research meant to study the effect of several particular factors on milk production in Malaysia. Another objective was to study the dynamic behaviour of lactation curve of goats by modelling approach. In order to gain the objectives, a few steps of study were taken. The first study was to identify the energy requirement of goats at the maintenance level. The second study aims to identify the content and the production of goats' milk. The next step was constructing a model of milk production system of goats based on reports made by previous researchers and the results obtained from the current studies. To validate the model constructed, validation steps were taken by comparing simulation data to the actual data on milk production system of goats. The initial study was conducted on 8 non lactating adult Saanen goats which were reared by the intensive system. The goats were fed with oil palm frond leaflet silage mixed with 5% DM molasses (OPFL) and also concentrate as supplement. The feed offered was adjusted in order to maintain the body weight. Later, an experiment was carried out to identify the digestibility of feed offered by using 6 goats from the same group. The second experiment was conducted on 17 adults, lactating goats reared by intensive system. The goats were also fed with OPFL silage and 33.6% of DM concentrate (in the diet) as supplement. The result of the research shows that the dry matter digestibility of feed with 77% of DM OPFL silage and 23% of DM concentarate by the Saanen goats was 44.1% whereas the dry matter intake was 3% of body weight. The energy requirement for maintenance was 433.3 kJ ME/kg BWo.75/day. The model developed was based on the energy utilization in the body system of goats. There were 4 main parameters considered in the model which influence the energy utilization for milk production. The parameters are feed intake, digestibility of feed, energy requirement for maintenance and energy conversion factor into milk production. The metabolizable energy consumption of goats can be estimated using the equation, MEvi = FI x DMD x 1 4.94, where FI is dry matter intake (kg/day), DMD is dry matter digestibility and 14.94 is the metabolizable energy value in feed (MJ/kgDM). The metabolizable energy requirement for maintenance for goats can be estimated using the equation MERm = MEmbw x MBW, where MEmbw is metabolizable energy for maintenance per metabolic body weight (MJ/kgBWo.75/day) and MBW is metabolic body weight. For goats in intensive system, MEmbw = 0.4333, however for grazing goats, MEmbw = 0.5416. The lactation curve and milk production can be estimated using the equation, y = a x nb x e(-c x n), where y is an average daily milk production, n is lactation week, a, b and c are constant. Metabolizable energy requirement for milk production can be estimated using the equation, MERI = 2.78 x MY/(0.463 + 0.1944 x DMD), where 2.78 is milk energy (MJ/kg) and MY is milk production (kg). The dry matter intake can be estimated using the equation, PI = (MEmbw x MBW + 2.78 x MY /(0.463 + 0.1944 x DMD))/( 1 4.94 X DMD). In general , milk production in the Malaysian production system can be represented by the mathematical equation: MY = ((14.94 x PI x DMD - MEmbw x MBW) x (0.463 + 0. 1 944 x DMD))/ 2.78. Assesment made on the Malaysian milk production system reveals that the main factors which effect milk production are breed and nutrition. B reeds that are suitable for producing milk in high quantity are dairy breeds which have the ability to adapt themselves with the environment in Malaysia. This study also finds that most of livestock feed sources in Malaysia has low or moderate in nutritive value. As a result, they are not suitable for high milk production. However, some of the sources such as oil palm frond (OPF) can be obtained from agricultural by-products. They are more suitable because the cost is cheaper and they can be obtained in a great quantity. In order to increase milk production, high quantity of concentrate should be given in the livestock feed. The model constructed is able to helps farmers in planning and managing their farms. It enables farmers to predict feed requirement, milk production and financial requirement for the dairy herds. Indirectly, this will improve the goats milk production in Malaysia.